Qahtaba bin Shabib Al-Tai, his biography and military role in the establishment of the Abbasid state (Journal of the College of Basic Education, 2023)
Qahtaba bin Shabib al-Ta’i is considered one of the brave leaders in the Abbasid call, as he began his political life as one of the Abbasid preachers in Khurasan and played an important role in consolidating the pillars of the call there. And he was rarely left behind from throwing them, so they realized his activity and his mission, in addition to his sincerity to the call, so they entrusted him with the leadership of the Abbasid army, and Qahtaba and his son Al-Hasan were able to subjugate the cities of Khorasan and other regions to his influence, and he showed great ingenuity in leading the Abbasid army and achieving great victories over the Umayyad army, and in the end the Abbasid army entered Iraq However, Qahtaba was lost in one of these battles, and thus the life of this great leader ended.